The Economic Impact of Medicaid Expansion on Pennsylvania - Price, Carter C. (RAND Corporation, 2013)
The Affordable Care Act is a substantial reform of the U.S. health care insurance system. Using the RAND COMPARE model, researchers assessed the act's potential economic effects on Pennsylvania, factoring in an optional expansion of Medicaid, and found the state would enjoy significant net benefits, including a growth of $3 billion in the state's GDP annually and more than 35,000 jobs.